Yellowing-resistant TPU vamp material and preparation method thereof

By combining TPU surface material with yarn, foaming molding, and using specific additives, the problems of color fastness and yellowing resistance of TPU shoe upper materials have been solved, resulting in a significant improvement in material performance.

CN120988337AInactive Publication Date: 2025-11-21JINJIANG MINGREN SHOE MATERIAL
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511508690.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-22
Publication Date
2025-11-21
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing TPU shoe upper materials have poor color fastness, insufficient resistance to sweat stains, light fastness, yellowing, and surface coating fastness, making it difficult to achieve a coordinated and comprehensive improvement in performance.

Method used

The preparation method adopts TPU surface material and filament composite foaming molding, combined with the use of antioxidants, lubricants, anti-yellowing agents, toughening agents and specific additives, including the co-formulation improvement of boron nitride-titanium dioxide and graphene liquid, to enhance the material performance.

Benefits of technology

Significantly improved colorfastness performance of TPU shoe upper materials, including resistance to sweat stains, light, yellowing, and surface coating, achieving a coordinated and comprehensive improvement in performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention relates to the technical field of TPU vamp materials, in particular to an anti-yellowing TPU vamp material and a preparation method thereof, and the preparation method comprises the following steps: weighing the following raw materials of a TPU surface layer in parts by weight: 55-65 parts of TPU, 8-11 parts of a first additive, 6-9 parts of a second additive, 3-5 parts of an antioxidant, 3-5 parts of a lubricant, 3-5 parts of an anti-yellowing agent, 3-5 parts of a flexibilizer and 2-4 parts of a silane coupling agent KH560; according to the yellowing-resistant TPU vamp material, the TPU surface layer raw materials are adopted and matched with the silk threads, the TPU vamp material is obtained through compounding of an extruder, foaming forming and final weaving forming, the first additive and the second additive are added for mutual blending, synergistic effect and common enhancement, the obtained TPU vamp material is excellent in color fastness, the perspiration resistance and the color fastness to light of the product are remarkable, and the yellowing-resistant TPU vamp material is suitable for being used in the field of shoes. Meanwhile, the product is excellent in yellowing resistance, folding resistance and surface coating fastness, and the product realizes coordinated and comprehensive performance improvement.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of TPU shoe upper material technology, specifically to a yellowing-resistant TPU shoe upper material and its preparation method. Background Technology

[0002] Thermoplastic polyurethane elastomer (TPU) is a polymer material that falls between rubber and plastic, and is widely used in the preparation of shoe upper materials. Compared to traditional shoe upper materials such as leather and canvas, TPU can meet the durability and functionality requirements of various footwear types, including athletic shoes and casual shoes. However, existing TPU shoe upper materials suffer from poor colorfastness, exhibiting poor resistance to sweat and light, as well as poor resistance to yellowing, flexural strength, and surface coating adhesion. This makes it difficult to achieve comprehensive and coordinated performance improvements, thus limiting the efficiency of shoe upper material use. Summary of the Invention

[0003] In view of the shortcomings of the prior art, the purpose of this invention is to provide a yellowing-resistant TPU shoe upper material and its preparation method, so as to solve the problems mentioned in the background art.

[0004] The present invention solves the technical problem by adopting the following technical solution: This invention provides a method for preparing a yellowing-resistant TPU shoe upper material, comprising the following steps: Step 1: Weigh the raw materials for the TPU surface layer according to the following weight proportions: 55-65 parts TPU, 8-11 parts first additive, 6-9 parts second additive, 3-5 parts antioxidant, 3-5 parts lubricant, 3-5 parts anti-yellowing agent, 3-5 parts toughening agent, and 2-4 parts silane coupling agent KH5602. Step 2: Mix the TPU surface material evenly and then feed it into the extruder. Preheat the extruder head to 190°C so that the TPU surface material is extruded in a molten viscous flow state. Pass the filament through the nozzle of the extruder head so that the viscous flow TPU surface material is coated on the outer periphery of the filament, and the TPU surface layer is formed by bonding on the outer periphery of the filament. Step 3: Foam the TPU outer layer of the yarn to obtain a TPU yarn body; then weave the TPU yarn body to obtain a yellowing-resistant TPU shoe upper material.

[0005] Preferably, the antioxidant is antioxidant 1010; the lubricant is zinc stearate; the toughening agent is dioctyl adipate; the anti-yellowing agent is UV-328; and the TPU is polyester-type TPU with a hardness of 85-95A. The foaming process begins with carbon dioxide as the fluid medium, at a pressure of 36-37 MPa and a temperature of 70-75℃ for 2 hours. Then, the pressure is rapidly released, the product is removed, and steam is introduced to maintain a pressure of 0.2-0.3 MPa. The temperature is then increased to foam the TPU surface layer for 40-45 minutes, resulting in a TPU surface layer thickness of 1.5-1.6 mm.

[0006] Preferably, the preparation method of the first additive is as follows: S1, Silane coupling agent KH550, aqueous ethanol solution and sodium lignosulfonate are mixed evenly in a weight ratio of (3-5):7:(1-2) to obtain a refolding agent; S2, 3-5 parts by weight of boron nitride, 2-4 parts by weight of mullite whiskers and 2-3 parts by weight of quartz powder are blended and sintered for 1 hour at a sintering temperature of 350-370℃. After sintering, a blend is obtained. The blend and a refolding agent are ultrasonically treated at a weight ratio of 5:(8-11). After ultrasonic treatment, a boron nitride-doped refolding liquid is obtained. S3, preheat titanium dioxide at 55-60℃ for 1h to obtain preheated titanium dioxide; stir the preheated titanium dioxide and boron nitride-doped refolding liquid at a weight ratio of 3:(5-7) until the stirring is finished to obtain boron nitride-titanium dioxide liquid. S4. Add boron nitride-titanium dioxide liquid to the first material at a weight ratio of (7-11):5 and ball mill at a speed of 1000-1500 r / min for 1 hour. After ball milling, filter and dry to obtain the first additive.

[0007] Preferably, the mass fraction of the ethanol-water solution is 75-85%; the ultrasonic power of the ultrasonic treatment is 350-400W, and the ultrasonic treatment lasts for 1 hour; the stirring speed of the stirring treatment is 450-550 r / min, and the stirring lasts for 2 hours.

[0008] Preferably, the preparation method of the first additive is as follows: Sodium citrate solution, nanocellulose and zirconium oxide are mixed evenly in a mass ratio of (5-8):3:(2-4) to obtain a feed solution; 3-5 parts by weight of zinc oxide, 2-3 parts by weight of silicon carbide and 2-3 parts by weight of basalt fiber are mixed and added to 8-12 parts by weight of the feed solution and stirred evenly, then filtered and dried to obtain the first feed material.

[0009] Preferably, the sodium citrate solution has a mass fraction of 10-15%.

[0010] Preferably, the preparation method of the second additive is as follows: S11: Stir graphene in a sodium dodecylbenzenesulfonate solution with a mass fraction of 8-12% (3-5 times the total weight of graphene) to obtain a graphene liquid. S02: Mix 2-3 parts by weight of hydroxyapatite, 3-5 parts by weight of hollow glass microspheres and 2-4 parts by weight of carbon nanotubes evenly to obtain a blend; add the blend to a dopamine hydrochloride solution with a mass fraction of 8-10% according to a weight ratio of 2:5, then add α-alumina powder with a mass fraction of 2-5% of the total weight of the dopamine hydrochloride solution, stir evenly to obtain an additive; S03: The additive and graphene liquid are mixed and ball-milled at a weight ratio of 5:(11-15), then filtered and dried to obtain the second additive.

[0011] Preferably, the ball milling speed for the blending ball milling process is 1000-1500 r / min, and the ball milling time is 2 h.

[0012] Preferably, the particle size of the α-alumina powder is 1.5-3.5 μm.

[0013] The present invention also provides a yellowing-resistant TPU shoe upper material, which is prepared by the preparation method of the aforementioned yellowing-resistant TPU shoe upper material.

[0014] Compared with the prior art, the present invention has the following beneficial effects: The TPU upper material of this invention, which is resistant to yellowing, uses TPU surface material, which is then combined with yarn through an extruder for compounding, foaming, and finally weaving to obtain the TPU upper material. The TPU in the surface material is the matrix, and antioxidants, lubricants, anti-yellowing agents, toughening agents, and silane coupling agent KH560 functional additives are added. At the same time, first additives and second additives are added to work together to enhance the color fastness of the TPU upper material. The product has significant effects on the color fastness to sweat and light, and at the same time, the product has excellent resistance to yellowing, flexural strength, and surface coating fastness. The product achieves a comprehensive improvement in performance coordination. The first additive uses preheated titanium dioxide, which is then stirred and improved with a boron nitride-doped refolding liquid. The boron nitride-doped refolding liquid is further optimized by ultrasonic blending of a blend and a refolding agent. In the blend, boron nitride, mullite whiskers, and quartz powder are blended and sintered, and then further blended with a refolding agent made from alkane coupling agent KH550, an ethanol aqueous solution, and sodium lignosulfonate. Through the improved blending of raw materials, the boron nitride-titanium dioxide liquid enhances the performance coordination of the product in the system. The first additive is then blended and added, where zinc oxide, silicon carbide, and basalt fiber are added for improved synergy. Sodium citrate solution, nanocellulose, and zirconium oxide are further blended and optimized. Through the improved blending of raw materials, a further blended boron nitride-titanium dioxide liquid is prepared, thus the first additive further enhances the performance of the product in the system. The second additive uses graphene dispersed in sodium dodecylbenzenesulfonate solution and further ball-milled with additives. The additives are blended with dopamine hydrochloride solution and α-alumina powder. Through the synergistic effect of the raw materials and the coordinated action of hydroxyapatite, hollow glass microspheres, and carbon nanotubes in the additives, the second additive is better synergistic with the first additive, thus further improving the product's performance. Detailed Implementation

[0015] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to specific examples. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0016] This embodiment describes a method for preparing a yellowing-resistant TPU shoe upper material, comprising the following steps: Step 1: Weigh the raw materials for the TPU surface layer according to the following weight proportions: 55-65 parts TPU, 8-11 parts first additive, 6-9 parts second additive, 3-5 parts antioxidant, 3-5 parts lubricant, 3-5 parts anti-yellowing agent, 3-5 parts toughening agent, and 2-4 parts silane coupling agent KH5602. Step 2: Mix the TPU surface material evenly and then feed it into the extruder. Preheat the extruder head to 190°C so that the TPU surface material is extruded in a molten viscous flow state. Pass the filament through the nozzle of the extruder head so that the viscous flow TPU surface material is coated on the outer periphery of the filament, and the TPU surface layer is formed by bonding on the outer periphery of the filament. Step 3: Foam the TPU outer layer of the yarn to obtain a TPU yarn body; then weave the TPU yarn body to obtain a yellowing-resistant TPU shoe upper material.

[0017] In this embodiment, the antioxidant is antioxidant 1010; the lubricant is zinc stearate; the toughening agent is dioctyl adipate; the anti-yellowing agent is UV-328; and the TPU is polyester-type TPU with a hardness of 85-95A. The foaming process begins with carbon dioxide as the fluid medium, at a pressure of 36-37 MPa and a temperature of 70-75℃ for 2 hours. Then, the pressure is rapidly released, the product is removed, and steam is introduced to maintain a pressure of 0.2-0.3 MPa. The temperature is then increased to foam the TPU surface layer for 40-45 minutes, resulting in a TPU surface layer thickness of 1.5-1.6 mm.

[0018] The preparation method of the first additive in this embodiment is as follows: S1, Silane coupling agent KH550, aqueous ethanol solution and sodium lignosulfonate are mixed evenly in a weight ratio of (3-5):7:(1-2) to obtain a refolding agent; S2, 3-5 parts by weight of boron nitride, 2-4 parts by weight of mullite whiskers and 2-3 parts by weight of quartz powder are blended and sintered for 1 hour at a sintering temperature of 350-370℃. After sintering, a blend is obtained. The blend and a refolding agent are ultrasonically treated at a weight ratio of 5:(8-11). After ultrasonic treatment, a boron nitride-doped refolding liquid is obtained. S3, preheat titanium dioxide at 55-60℃ for 1h to obtain preheated titanium dioxide; stir the preheated titanium dioxide and boron nitride-doped refolding liquid at a weight ratio of 3:(5-7) until the stirring is finished to obtain boron nitride-titanium dioxide liquid. S4. Add boron nitride-titanium dioxide liquid to the first material at a weight ratio of (7-11):5 and ball mill at a speed of 1000-1500 r / min for 1 hour. After ball milling, filter and dry to obtain the first additive.

[0019] In this embodiment, the mass fraction of the ethanol-water solution is 75-85%; the ultrasonic power of the ultrasonic treatment is 350-400W, and the ultrasonic treatment lasts for 1 hour; the stirring speed of the stirring treatment is 450-550 r / min, and the stirring lasts for 2 hours.

[0020] The preparation method for adding the first material in this embodiment is as follows: Sodium citrate solution, nanocellulose and zirconium oxide are mixed evenly in a mass ratio of (5-8):3:(2-4) to obtain a feed solution; 3-5 parts by weight of zinc oxide, 2-3 parts by weight of silicon carbide and 2-3 parts by weight of basalt fiber are mixed and added to 8-12 parts by weight of the feed solution and stirred evenly, then filtered and dried to obtain the first feed material.

[0021] The sodium citrate solution in this embodiment has a mass fraction of 10-15%.

[0022] The preparation method of the second additive in this embodiment is as follows: S11: Stir graphene in a sodium dodecylbenzenesulfonate solution with a mass fraction of 8-12% (3-5 times the total weight of graphene) to obtain a graphene liquid. S02: Mix 2-3 parts by weight of hydroxyapatite, 3-5 parts by weight of hollow glass microspheres and 2-4 parts by weight of carbon nanotubes evenly to obtain a blend; add the blend to a dopamine hydrochloride solution with a mass fraction of 8-10% according to a weight ratio of 2:5, then add α-alumina powder with a mass fraction of 2-5% of the total weight of the dopamine hydrochloride solution, stir evenly to obtain an additive; S03: The additive and graphene liquid are mixed and ball-milled at a weight ratio of 5:(11-15), then filtered and dried to obtain the second additive.

[0023] In this embodiment, the ball milling speed for the blending ball milling process is 1000-1500 r / min, and the ball milling time is 2 hours.

[0024] The particle size of the α-alumina powder in this embodiment is 1.5-3.5 μm.

[0025] The TPU shoe upper material resistant to yellowing described in this embodiment is prepared by the method for preparing a TPU shoe upper material resistant to yellowing.

[0026] Example 1: A method for preparing a yellowing-resistant TPU shoe upper material, comprising the following steps: Step 1: Weigh the raw materials for the TPU surface layer according to the following weight proportions: 55 parts TPU, 8 parts first additive, 6 parts second additive, 3 parts antioxidant, 3 parts lubricant, 3 parts anti-yellowing agent, 3 parts toughening agent, and 2 parts silane coupling agent KH560. Step 2: Mix the TPU surface material evenly and then feed it into the extruder. Preheat the extruder head to 190°C so that the TPU surface material is extruded in a molten viscous flow state. Pass the filament through the nozzle of the extruder head so that the viscous flow TPU surface material is coated on the outer periphery of the filament, and the TPU surface layer is formed by bonding on the outer periphery of the filament. Step 3: Foam the TPU outer layer of the yarn to obtain a TPU yarn body; then weave the TPU yarn body to obtain a yellowing-resistant TPU shoe upper material.

[0027] In this embodiment, the antioxidant is antioxidant 1010; the lubricant is zinc stearate; the toughening agent is dioctyl adipate; the anti-yellowing agent is UV-328; and the TPU is polyester TPU with a hardness of 85A. The foaming process begins with carbon dioxide as the fluid medium, at a pressure of 36 MPa and a temperature of 70°C for 2 hours. Then, the pressure is rapidly released, the product is removed, and water vapor is introduced to maintain a pressure of 0.2 MPa. The temperature is then increased to foam the TPU surface layer for 40 minutes, resulting in a TPU surface layer thickness of 1.5 mm.

[0028] The preparation method of the first additive in this embodiment is as follows: S1, Silane coupling agent KH550, aqueous ethanol solution and sodium lignosulfonate are mixed evenly in a weight ratio of 3:7:1 to obtain a refolding agent; S2, 3 parts by weight of boron nitride, 2 parts by weight of mullite whiskers and 2 parts by weight of quartz powder are blended and sintered for 1 hour at a sintering temperature of 350℃. After sintering, a blend is obtained. The blend and a refolding agent are ultrasonically treated at a weight ratio of 5:8. After ultrasonic treatment, a boron nitride-doped refolding liquid is obtained. S3, preheat titanium dioxide at 55℃ for 1 hour to obtain preheated titanium dioxide; stir the preheated titanium dioxide and boron nitride-doped refolding solution at a weight ratio of 3:5 until the stirring is finished to obtain boron nitride-titanium dioxide solution. S4. Add boron nitride-titanium dioxide solution to the first material at a weight ratio of 7:5 and ball mill at a speed of 1000 r / min for 1 hour. After ball milling, filter and dry to obtain the first additive.

[0029] In this embodiment, the ethanol-water solution has a mass fraction of 75%; the ultrasonic power for the ultrasonic treatment is 350W, and the ultrasonic treatment lasts for 1 hour; the stirring speed for the stirring treatment is 450 r / min, and the stirring lasts for 2 hours.

[0030] The preparation method for adding the first material in this embodiment is as follows: Sodium citrate solution, nanocellulose, and zirconium oxide were mixed evenly in a mass ratio of 5:3:2 to obtain a filler solution. 3 parts by weight of zinc oxide, 2 parts by weight of silicon carbide, and 2 parts by weight of basalt fiber were mixed and added to 8 parts by weight of the filler solution and stirred evenly. Then, the mixture was filtered and dried to obtain the first filler material.

[0031] The sodium citrate solution in this embodiment has a mass fraction of 10%.

[0032] The preparation method of the second additive in this embodiment is as follows: S11: Graphene is stirred evenly in a sodium dodecylbenzenesulfonate solution with a mass fraction of 8% (3 times the total weight of graphene) to obtain a graphene liquid. S02: Mix 2 parts by weight of hydroxyapatite, 3 parts by weight of hollow glass microspheres and 2 parts by weight of carbon nanotubes evenly to obtain a blend; add the blend to an 8% by weight of dopamine hydrochloride solution at a weight ratio of 2:5, then add 2% by weight of α-alumina powder of the total weight of the dopamine hydrochloride solution, stir evenly to obtain an additive. S03: The additive and graphene liquid are mixed and ball-milled at a weight ratio of 5:11, then filtered and dried to obtain the second additive.

[0033] In this embodiment, the ball milling process for blending and ball milling is performed at a speed of 1000 r / min for 2 hours.

[0034] The particle size of the α-alumina powder in this embodiment is 1.5 μm.

[0035] The TPU shoe upper material resistant to yellowing described in this embodiment is prepared by the method for preparing a TPU shoe upper material resistant to yellowing.

[0036] Example 2: A method for preparing a yellowing-resistant TPU shoe upper material, comprising the following steps: Step 1: Weigh the raw materials for the TPU surface layer according to the following weight proportions: 65 parts TPU, 11 parts first additive, 9 parts second additive, 5 parts antioxidant, 5 parts lubricant, 5 parts anti-yellowing agent, 5 parts toughening agent, and 4 parts silane coupling agent KH560. Step 2: Mix the TPU surface material evenly and then feed it into the extruder. Preheat the extruder head to 190°C so that the TPU surface material is extruded in a molten viscous flow state. Pass the filament through the nozzle of the extruder head so that the viscous flow TPU surface material is coated on the outer periphery of the filament, and the TPU surface layer is formed by bonding on the outer periphery of the filament. Step 3: Foam the TPU outer layer of the yarn to obtain a TPU yarn body; then weave the TPU yarn body to obtain a yellowing-resistant TPU shoe upper material.

[0037] In this embodiment, the antioxidant is antioxidant 1010; the lubricant is zinc stearate; the toughening agent is dioctyl adipate; the anti-yellowing agent is UV-328; and the TPU is polyester TPU with a hardness of 95A. The foaming process first uses carbon dioxide as the fluid medium, with a pressure of 37 MPa, a temperature of 75°C, and a time of 2 hours. Then, the pressure is rapidly released, the product is removed, and water vapor is introduced to maintain a pressure of 0.3 MPa. The temperature is then increased to foam the TPU surface layer for 45 minutes, resulting in a TPU surface layer thickness of 1.6 mm.

[0038] The preparation method of the first additive in this embodiment is as follows: S1, Silane coupling agent KH550, aqueous ethanol solution and sodium lignosulfonate are mixed evenly in a weight ratio of 5:7:2 to obtain a refolding agent; S2, 5 parts by weight of boron nitride, 4 parts by weight of mullite whiskers and 3 parts by weight of quartz powder are blended and sintered for 1 hour at a sintering temperature of 370℃. After sintering, a blend is obtained. The blend and a refolding agent are ultrasonically treated at a weight ratio of 5:11. After ultrasonic treatment, a boron nitride-doped refolding liquid is obtained. S3, preheat titanium dioxide at 60℃ for 1 hour to obtain preheated titanium dioxide; stir the preheated titanium dioxide and boron nitride-doped refolding solution at a weight ratio of 3:7 until the stirring is finished to obtain boron nitride-titanium dioxide solution. S4. Add boron nitride-titanium dioxide liquid to the first material at a weight ratio of 11:5 and ball mill at a speed of 1500 r / min for 1 hour. After ball milling, filter and dry to obtain the first additive.

[0039] In this embodiment, the ethanol-water solution has a mass fraction of 85%; the ultrasonic power for the ultrasonic treatment is 400W, and the ultrasonic treatment lasts for 1 hour; the stirring speed for the stirring treatment is 550 r / min, and the stirring lasts for 2 hours.

[0040] The preparation method for adding the first material in this embodiment is as follows: Sodium citrate solution, nanocellulose, and zirconium oxide were mixed evenly in a mass ratio of 8:3:4 to obtain a feed solution. 5 parts by weight of zinc oxide, 3 parts by weight of silicon carbide, and 3 parts by weight of basalt fiber were mixed and added to 12 parts by weight of the feed solution and stirred evenly. Then, the mixture was filtered and dried to obtain the first feed material.

[0041] The sodium citrate solution in this embodiment has a mass fraction of 15%.

[0042] The preparation method of the second additive in this embodiment is as follows: S11: Graphene is stirred evenly in a sodium dodecylbenzenesulfonate solution with a mass fraction of 12% (5 times the total weight of graphene) to obtain a graphene liquid. S02: Mix 3 parts by weight of hydroxyapatite, 5 parts by weight of hollow glass microspheres and 4 parts by weight of carbon nanotubes evenly to obtain a blend; add the blend to a 10% by weight of dopamine hydrochloride solution at a weight ratio of 2:5, then add 5% by weight of α-alumina powder of the total weight of the dopamine hydrochloride solution, stir evenly to obtain an additive. S03: The additive and graphene liquid are mixed and ball-milled at a weight ratio of 5:15, then filtered and dried to obtain the second additive.

[0043] In this embodiment, the ball milling process for blending and ball milling is performed at a speed of 1500 r / min for 2 hours.

[0044] The particle size of the α-alumina powder in this embodiment is 3.5 μm.

[0045] The TPU shoe upper material resistant to yellowing described in this embodiment is prepared by the method for preparing a TPU shoe upper material resistant to yellowing.

[0046] Example 3: A method for preparing a yellowing-resistant TPU shoe upper material, comprising the following steps: Step 1: Weigh the raw materials for the TPU surface layer according to the following weight proportions: 60 parts TPU, 9 parts first additive, 7.5 parts second additive, 4 parts antioxidant, 4 parts lubricant, 4 parts anti-yellowing agent, 4 parts toughening agent, and 3 parts silane coupling agent KH560. Step 2: Mix the TPU surface material evenly and then feed it into the extruder. Preheat the extruder head to 190°C so that the TPU surface material is extruded in a molten viscous flow state. Pass the filament through the nozzle of the extruder head so that the viscous flow TPU surface material is coated on the outer periphery of the filament, and the TPU surface layer is formed by bonding on the outer periphery of the filament. Step 3: Foam the TPU outer layer of the yarn to obtain a TPU yarn body; then weave the TPU yarn body to obtain a yellowing-resistant TPU shoe upper material.

[0047] In this embodiment, the antioxidant is antioxidant 1010; the lubricant is zinc stearate; the toughening agent is dioctyl adipate; the anti-yellowing agent is UV-328; and the TPU is polyester TPU with a hardness of 90A. The foaming process first uses carbon dioxide as the fluid medium, with a pressure of 36.5 MPa, a temperature of 72°C, and a time of 2 hours. Then, the pressure is rapidly released, the product is removed, and water vapor is introduced to maintain a pressure of 0.25 MPa. The temperature is then increased to foam the TPU surface layer for 42.5 minutes, resulting in a TPU surface layer thickness of 1.55 mm.

[0048] The preparation method of the first additive in this embodiment is as follows: S1, Silane coupling agent KH550, aqueous ethanol solution and sodium lignosulfonate are mixed evenly in a weight ratio of 4:7:1.5 to obtain a refolding agent; S2, 4 parts by weight of boron nitride, 3 parts by weight of mullite whiskers and 2.5 parts by weight of quartz powder are blended and sintered for 1 hour at a sintering temperature of 360°C. After sintering, a blend is obtained. The blend and a refolding agent are ultrasonically treated at a weight ratio of 5:9. After ultrasonic treatment, a boron nitride-doped refolding liquid is obtained. S3, preheat titanium dioxide at 58℃ for 1 hour to obtain preheated titanium dioxide; stir the preheated titanium dioxide and boron nitride-doped refolding solution at a weight ratio of 3:6 until the stirring is finished to obtain boron nitride-titanium dioxide solution. S4. Add boron nitride-titanium dioxide solution to the first material at a weight ratio of 9:5 and ball mill at a speed of 1250 r / min for 1 hour. After ball milling, filter and dry to obtain the first additive.

[0049] In this embodiment, the ethanol-water solution has a mass fraction of 80%; the ultrasonic power for the ultrasonic treatment is 375W, and the ultrasonic treatment lasts for 1 hour; the stirring speed for the stirring treatment is 500 r / min, and the stirring lasts for 2 hours.

[0050] The preparation method for adding the first material in this embodiment is as follows: Sodium citrate solution, nanocellulose, and zirconium oxide were mixed evenly in a mass ratio of 6.5:3:3 to obtain a filler solution. Four parts by weight of zinc oxide, 2.5 parts by weight of silicon carbide, and 2.5 parts by weight of basalt fiber were added to 10 parts by weight of the filler solution and stirred evenly. The mixture was then filtered and dried to obtain the first filler material.

[0051] The sodium citrate solution in this embodiment has a mass fraction of 12.5%.

[0052] The preparation method of the second additive in this embodiment is as follows: S11: Graphene is stirred evenly in a sodium dodecylbenzenesulfonate solution with a mass fraction of 10% (4 times the total weight of graphene) to obtain a graphene liquid. S02: 2.5 parts by weight of hydroxyapatite, 4 parts by weight of hollow glass microspheres and 3 parts by weight of carbon nanotubes are mixed evenly to obtain a blend; the blend is added to a 9% by weight of dopamine hydrochloride solution at a weight ratio of 2:5, and then 3.5% by weight of α-alumina powder of the total weight of dopamine hydrochloride solution is added and stirred evenly to obtain an additive; S03: The additive and graphene liquid are mixed and ball-milled at a weight ratio of 5:13, then filtered and dried to obtain the second additive.

[0053] In this embodiment, the ball milling process for blending and ball milling is performed at a speed of 1250 r / min for 2 hours.

[0054] The particle size of the α-alumina powder in this embodiment is 2.0 μm.

[0055] The TPU shoe upper material resistant to yellowing described in this embodiment is prepared by the method for preparing a TPU shoe upper material resistant to yellowing.

[0056] Comparative Example 1: Unlike Example 3, no first additive was added.

[0057] Comparative Example 2: Unlike Example 3, boron nitride-titanium dioxide solution was not added in the preparation of the first additive.

[0058] Comparative Example 3: Unlike Example 3, preheated titanium dioxide was not added in the preparation of the boron nitride-titanium dioxide solution.

[0059] Comparative Example 4: Unlike Example 3, no boron nitride-doped refolding solution was added in the preparation of the boron nitride-titanium dioxide solution.

[0060] Comparative Example 5: Unlike Example 3, no blend was added in the preparation of the boron nitride-doped refolding solution.

[0061] Comparative Example 6: Unlike Example 3, no mullite whiskers and quartz powder were added to the blend.

[0062] Comparative Example 7: Unlike Example 3, the first additive was not added during the preparation of the first additive.

[0063] Comparative Example 8: Unlike Example 3, no second additive was added.

[0064] Comparative Example 9: Unlike Example 3, no graphene liquid was added in the preparation of the second additive.

[0065] Comparative Example 10: Unlike Example 3, no additives were added in the preparation of the second additive.

[0066] Comparative Example 11: Unlike Example 3, no blending material was added to the additives.

[0067] Comparative Example 12: Unlike Example 3, hollow glass microspheres and carbon nanotubes were not added to the blend.

[0068] Comparative Example 13: Unlike Example 3, α-alumina powder was not added to the additives, and water was used instead of dopamine hydrochloride solution.

[0069] The product performance of Examples 1-3 and Comparative Examples 1-13 was tested for: color fastness to perspiration (GB / T3922-2013 standard test), color fastness to light (J52 C method spotlight, irradiation distance 0.5mm, continuous irradiation for 72h), resistance to yellowing (GB / T29778-2013 Textiles color fastness test, assessment of potential phenolic yellowing), folding endurance (J66 A method, room temperature, 40,000 cycles, no cracking, blistering, or delamination should occur), and surface coating fastness (J69 dry rubbing 100 cycles, no wear or peeling of surface coating). The test results are shown in Table 1.

[0070] Table 1. Product performance test results of Examples 1-3 and Comparative Examples 1-13: As can be seen from Comparative Examples 1-13 and Examples 1-3, the product of Example 3 has excellent color fastness performance. The product has significant effects on the color fastness to perspiration and light. At the same time, the product has excellent resistance to yellowing, folding resistance and surface coating fastness. The product achieves a comprehensive improvement in performance coordination. As can be seen from Comparative Examples 1-13 and Example 3, the performance of the product deteriorates significantly when neither the first additive nor the second additive is added. The product performance is most significantly improved when the first additive and the second additive are blended and synergistically combined. The first additive was not prepared without boron nitride-titanium dioxide liquid, preheated titanium dioxide was not added, boron nitride-doped compounding liquid was not added, a blend was not added, mullite whiskers and quartz powder were not added, and the first additive was not added. All these factors resulted in varying degrees of deterioration in the product's performance. The first additive, prepared by combining boron nitride-titanium dioxide liquid obtained using the specific method of this invention with the first additive, exhibited the most significant performance improvement. Other methods were not as effective as those of this invention. In the preparation of the second additive, no graphene liquid was added, no additives were added, no blending material was added to the additives, no hollow glass microspheres and carbon nanotubes were added to the blending material, and no α-alumina powder and dopamine hydrochloride solution were added to the additives; water was used instead. The performance of the product tended to deteriorate in all these cases. Only the second additive prepared by the method of the present invention showed the most significant performance effect. Other methods were not as effective as the present invention.

[0071] Based on the above research, this invention further explores the product performance by adding a first ingredient during preparation.

[0072] Experimental Example 1: Same as Example 3, except that silicon carbide was not added in the preparation of the first material.

[0073] Experimental Example 2: Same as Example 3, except that basalt fiber silicon was not added in the preparation of the first material.

[0074] Experimental Example 3: Same as Example 3, except that nanocellulose was not added to the feed solution.

[0075] Experiment Example 4: Same as Example 3, except that zirconium oxide was not added to the feed solution.

[0076] The product performance of Experiment 1-4 was tested in the same way, and the test results are shown in Table 2.

[0077] Table 2. Product performance test results for Experiment Examples 1-4: As can be seen from Experiments 1-4, the performance of the products deteriorated when silicon carbide, basalt fiber, nanocellulose, or zirconium oxide were not added during the preparation of the first additive, the preparation of the first additive, the preparation of the first additive, and the preparation of the first additive by different methods. The performance of the products deteriorated to varying degrees when the first additive was prepared by the specific method of this invention. The product performance was the most significantly improved when the first additive was prepared by the specific method of this invention.

[0078] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from the spirit or essential characteristics of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description. Thus, it is intended that all variations falling within the meaning and scope of equivalents of the claims be included within the present invention.

[0079] Furthermore, it should be understood that although this specification describes embodiments, not every embodiment contains only one independent technical solution. This narrative style is merely for clarity. Those skilled in the art should consider the specification as a whole, and the technical solutions in each embodiment can also be appropriately combined to form other embodiments that can be understood by those skilled in the art.

Claims

1. A method for preparing a yellowing-resistant TPU shoe upper material, characterized in that, Includes the following steps: Step 1: Weigh the raw materials for the TPU surface layer according to the following weight proportions: TPU 55-65 parts, first additive 8-11 parts, second additive 6-9 parts, antioxidant 3-5 parts, lubricant 3-5 parts, anti-yellowing agent 3-5 parts, toughening agent 3-5 parts, silane coupling agent KH560 2-4 parts. The preparation method of the first additive is as follows: S1, Silane coupling agent KH550, aqueous ethanol solution and sodium lignosulfonate are mixed evenly in a weight ratio of (3-5):7:(1-2) to obtain a refolding agent; S2, 3-5 parts by weight of boron nitride, 2-4 parts by weight of mullite whiskers and 2-3 parts by weight of quartz powder are blended and sintered for 1 hour at a sintering temperature of 350-370℃. After sintering, a blend is obtained. The blend and a refolding agent are ultrasonically treated at a weight ratio of 5:(8-11). After ultrasonic treatment, a boron nitride-doped refolding liquid is obtained. S3, preheat titanium dioxide at 55-60℃ for 1h to obtain preheated titanium dioxide; stir the preheated titanium dioxide and boron nitride-doped refolding liquid at a weight ratio of 3:(5-7) until the stirring is finished to obtain boron nitride-titanium dioxide liquid. S4. Add boron nitride-titanium dioxide liquid to the first material at a weight ratio of (7-11):5 and ball mill at a speed of 1000-1500 r / min for 1 hour. After ball milling, filter and dry to obtain the first additive. Step 2: Mix the TPU surface material evenly and then feed it into the extruder. Preheat the extruder head to 190°C so that the TPU surface material is extruded in a molten viscous flow state. Pass the filament through the nozzle of the extruder head so that the viscous flow TPU surface material is coated on the outer periphery of the filament, and the TPU surface layer is formed by bonding on the outer periphery of the filament. Step 3: Foam the TPU outer layer of the yarn to obtain a TPU yarn body; then weave the TPU yarn body to obtain a yellowing-resistant TPU shoe upper material.

2. The method for preparing a yellowing-resistant TPU shoe upper material according to claim 1, characterized in that, The antioxidant is antioxidant 1010; the lubricant is zinc stearate; the toughening agent is dioctyl adipate; the anti-yellowing agent is UV-328; and the TPU is polyester-type TPU with a hardness of 85-95A. The foaming process begins with carbon dioxide as the fluid medium, at a pressure of 36-37 MPa and a temperature of 70-75℃ for 2 hours. Then, the pressure is rapidly released, the product is removed, and steam is introduced to maintain a pressure of 0.2-0.3 MPa. The temperature is then increased to foam the TPU surface layer for 40-45 minutes, resulting in a TPU surface layer thickness of 1.5-1.6 mm.

3. The method for preparing a yellowing-resistant TPU shoe upper material according to claim 1, characterized in that, The ethanol-water solution has a mass fraction of 75-85%; the ultrasonic power for the ultrasonic treatment is 350-400W, and the ultrasonic treatment lasts for 1 hour; the stirring speed for the stirring treatment is 450-550 r / min, and the stirring lasts for 2 hours.

4. The method for preparing a yellowing-resistant TPU shoe upper material according to claim 1, characterized in that, The preparation method of the first additive is as follows: Sodium citrate solution, nanocellulose and zirconium oxide are mixed evenly in a mass ratio of (5-8):3:(2-4) to obtain a feed solution; 3-5 parts by weight of zinc oxide, 2-3 parts by weight of silicon carbide and 2-3 parts by weight of basalt fiber are mixed and added to 8-12 parts by weight of the feed solution and stirred evenly, then filtered and dried to obtain the first feed material.

5. The method for preparing a yellowing-resistant TPU shoe upper material according to claim 4, characterized in that, The sodium citrate solution has a mass fraction of 10-15%.

6. The method for preparing a yellowing-resistant TPU shoe upper material according to claim 1, characterized in that, The preparation method of the second additive is as follows: S11: Stir graphene in a sodium dodecylbenzenesulfonate solution with a mass fraction of 8-12% (3-5 times the total weight of graphene) to obtain a graphene liquid. S02: Mix 2-3 parts by weight of hydroxyapatite, 3-5 parts by weight of hollow glass microspheres and 2-4 parts by weight of carbon nanotubes evenly to obtain a blend; add the blend to a dopamine hydrochloride solution with a mass fraction of 8-10% according to a weight ratio of 2:5, then add α-alumina powder with a mass fraction of 2-5% of the total weight of the dopamine hydrochloride solution, stir evenly to obtain an additive; S03: The additive and graphene liquid are mixed and ball-milled at a weight ratio of 5:(11-15), then filtered and dried to obtain the second additive.

7. The method for preparing a yellowing-resistant TPU shoe upper material according to claim 6, characterized in that, The ball milling process for the blending treatment is carried out at a speed of 1000-1500 r / min for 2 hours.

8. The method for preparing a yellowing-resistant TPU shoe upper material according to claim 6, characterized in that, The particle size of the α-alumina powder is 1.5-3.5 μm.

9. A yellowing-resistant TPU shoe upper material, prepared by the preparation method of a yellowing-resistant TPU shoe upper material as described in any one of claims 1 to 8.